Systematic Investigation of the Efficacy of Sinitang Decoction Against Ulcerative Colitis - Enhui Ji; Enhui Ji; Tingting Wang; Jing Xu; Jianwei Fan; Yi Zhang; Yongxia Guan; Hongjun Yang; Junying Wei; Guimin Zhang; Luqi Huang; Luqi Huang (Frontiers Media S.A., 2020)
The aim of this study was to investigate the precise clinical use of Sinitang decoction (SNT) in ulcerative colitis (UC). Network pharmacology-based analysis of the drug components-targets-diseases-pathways was used to predict the possible clinical applications of SNT. Next, 2,4,6-trinitrobenzenesulfonic acid (TNBS) was used to establish a rat model of UC, and the efficacy of SNT against UC was tested, followed by a proteomic analysis of the specific signatures regulated by SNT against UC. SNT was predicted to be effective in inflammatory bowel disease, UC, and several other diseases. In the rats with UC, SNT decreased the disease activity index and colon mucosal damage index compared to the untreated UC model rats. Additionally, SNT reversed the upregulated levels of serum tumor necrosis factor (TNF)-α, prostaglandin E2 (PGE2), interleukin (IL)-6, and nitric oxide (NO) in UC model rats. The proteomic analysis identified 78 proteins that were differentially regulated by SNT in the rats with UC, which were associated with the Gene Ontology terms sulfur compound binding, calcium ion binding, and Toll-like receptor (TLR)-4 binding. Among these differentially regulated proteins, C-reactive protein (CRP) and collagen alpha-1(XII) chain (COL12A1) were found to be signature proteins associated with the efficacy of SNT against UC. This study represents the first precise investigation of the efficacy and mechanisms of SNT against UC, and shows that SNT is a promising candidate for personalized management of UC.